Diagnostic usefulness of 24‐h polysomnography for idiopathic hypersomnia co‐occurring with neurodevelopmental disorders: A case report - Keisuke Kido; Naoko Sugita; Toshiya Murai; Naoko Tachibana; Manabu Kubota (PCN Reports)
Abstract Background Although central disorders of hypersomnolence (CDH) and attention‐deficit/hyperactivity disorder (ADHD) are frequently comorbid, they often remain underdiagnosed, leading to insufficient treatment and sociopsychological outcomes. Case Presentation Here, we present a case of a male in his late 20s with ADHD and autism spectrum disorder who exhibited symptoms suggestive of idiopathic hypersomnia (IH), a subtype of CDH. The patient experienced difficulty waking up and dropped out of university. Additionally, although methylphenidate extended‐release was prescribed, he often forgot to take his medication, resulting in difficulty waking up until late afternoon. No symptoms related to rapid eye movements sleep were observed. Considering the possibility of concurrent hypersomnia with neurodevelopmental disorders, we conducted 24‐h polysomnography (PSG). The results demonstrated total sleep time of 774.5 min (≥660 min). Together with other criteria, we diagnosed him as having IH. Following discharge and discussion with the patient, we provided sleep hygiene education for him, and he resumed day care attendance to establish a social routine. Conclusion In cases where hypersomnia may co‐occur with neurodevelopmental disorders, active utilization of 24‐h PSG enables detailed evaluation of sleep–wake patterns and behaviors, facilitating effective guidance on sleep hygiene and promoting improvements in social rhythms and sociability.